Analisis Perhitungan HPP dengan Metode Full Costing dalam Menetapkan Harga Jual Produksi pada UMKM Martabak Manis Abang Adek Jakarta Barat: Analysis of HPP Calculation with the Full Costing Method in Determining Production Selling Price at Martabak Manis MSMEs Brother of the Brothers and Sisters of West Jakarta - Bernadeta Ade Reany; Redita Putri Sunja; Desi Desi; Najwa Putri Rahmawati; Raden Giezka Putri Widjaja (PT Cakrawarti Empat Proksi, 2026)
This study analyzes the calculation of Cost of Goods Sold (COGS) using the Full costing method at the Martabak Manis Abang Adek micro and small enterprise in West Jakarta to determine a more optimal selling price compared to the conventional method currently used by including all production cost elements, namely raw material costs (flour, sugar, eggs, and milk), direct labor cost, and factory overhead (electricity, gas, and rent), based on the enterprise’s monthly production data. The research uses a descriptive quantitative approach through direct observation and interviews to document cost components and pricing pratices. Finding indicate a significant difference between the conventional COGS calculated with full costing. By incorporating the comprehensive daily factory overhead, including equipment depreciation and rent, the total daily production cost is determined at Rp338,357,resulting in an accurate COGS of Rp3,562 per unit. This accurate cost allocation eliminates undercosting risks, providing a more realistic foundation tp ensure business viability. The study recommends that similar culinary SMEs adopt data driven full Costing to improve pricing decision and financial sustainability.